Personal Responsibility with Health. Differents Social Actors Knowledges and Perceptions - Isabel Pilar Luis Gonzálvez; Yusdany Torres Jiménez; Adolfo Álvarez Pérez (Revista Finlay)
Background: the updating process of the Cuban economic and social model support the need to ensure the proper balance between the responsibilities that concern the State and the Government and those corresponding to individuals. There has been a repositioning of the issue of personal responsibility with health at the national level, but the social representation of this term in different social actors that intervene in health governance at the community level, community and local level, is unknown. Objective: to explore the knowledge and perceptions that different social actors in the community have on personal responsibility with health. Method: a sample of 385 subjects from the Andrés Ortiz health area of the Guanabacoa municipality in Havana was selected using probabilistic and discretionary criteria, composed of professionals and technicians from the health sector, members of non-governmental organizations, political organizations, and the government local and citizens belonging to three clinics of primary health care. Instruments for data collection were built and validated. The information was obtained through semi-structured interviews and surveys. Discourse content analysis and descriptive data analysis were performed using absolute and relative frequencies. Result: the 100 % of professionals and technicians from the health sector, members of local government, political organizations and non-governmental organizations had previous references to the term, but only the 45 % of the public had heard about him. The sources of prior knowledge about the term differed among social actors. The perception that personal responsibility for health should be restricted to individual self-care was the majority mainly among citizens (83.4 %), representatives of non-governmental organizations (78 %), members of the local government and leaders of the health sector (62.5 %), technicians and health professionals (59 %) and, to a lesser proportion teachers in this sector (50 %). The 100 % of the representatives of the political organizations perceived that this responsibility should have an individual vision. Conclusions: there are differences of opinion in the representational field of personal responsibility with health among the different social actors consulted. The discursive and representational environment predominated, related to personal responsibility limited to individual health.